Analysis of Journalistic Students' Understanding of the Journalistic Profession in the Digital Age - Alya Fauzira Raynadel; Lita Ananta Putri; Wahyunengsih Wahyunengsih (KONTEKSTUAL : Jurnal Ilmu Komunikasi, 2022)
Digital journalism is actually an old form of journalism practice but in a new context. In digital journalism, social media serves to gather information and verify the sources of information. From what has been described in previous studies with our research, it can be concluded that they have similarities in researching journalism in the digital era, but what distinguishes us is analyzing Journalism Students in the Digital Era in detail and detail. Selecting Journalism Students as Research Subjects. The researcher uses the object, namely journalism in the digital era, and the subject is journalism students. We use quantitative methods. By conducting research by distributing questionnaires or questionnaires to be method we use, we give questionnaires to students who study journalism at various universities. This study aims to find out how the development of students in journalism in the digital era and see how the development of job prospects related to journalism in the digital era. this digital. The results of this study obtained several answers from respondents regarding the article Understanding Analysis of Journalism Students in the journalistic profession. Almost all of the results of this study were filled out through a questionnaire or questionnaire. Respondents (students) explained that many students from the journalism study program wanted the journalistic profession to develop more rapidly in this digital era, and the results of the research showed that many students were very enthusiastic about how this journalistic profession could open up employment opportunities for students who would later graduate. Bachelor’s degree and get a jobthat is in accordance with the study program that is carried out with ease. The results of this study also show that the solution to survive as a student so as not to be left behind in this digital age is to continue to follow the era or era that exists by developing and increasing creativity self.AbstrakJurnalisme digital sejatinya adalah bentuk praktik jurnalisme lama, namun dalam konteks yang baru. Dalam jurnalisme digital, media sosial berfungsi untuk mengumpulkan informasi dan memverifikasi sumber informasi. Dari yang sudah di uraikan penelitian terdahulu dengan penelitian kami dapat di simpulkan yaitu memeliki kesamaan dalam meneliti jurnalistik di era digital, tetapi yang membedakan kami menganalisis Mahasiswa Jurnalistik Di era Digital secara rinci dan detail. Memilih Mahasiswa jurnalistik Sebagai Subjek peneliti. peneliti Memakai Objek yaitu Jurnalisme diera digital Dan Subjek nya yaitu Mahasiswa Jurnalistik. Kami memakai metode kuantitatif. Dengan melalukan penelitian dengan cara menyebarkan angket atau quisioner untuk menjadi metode yang kami pakai, kami memberi angket kepada mahasiswa mahasiswa yang berprodi jurnalistik di berbagai universitas. Penelitian ini bertujuan Untuk mengetahui bagaimana perkembangan mahasiswa di jurnalistik di era digital dan melihat bagaimana perkembangan prospek kerja yang berhubungan dengan jurnalistik di era digital, Kami mendapat referensi untuk membuat penelitian ini dan meneliti ke berbagai mahasiswa dari buku buku para ahli yang menjelaskan tentang jurnalistik di era digitalini.Hasil penelitian tersebut mendapatkan beberapa jawaban dari responden mengenai artikel Analisis Pemahaman Mahasiswa Jurnalistik pada profesi jurnalistik, Hampir semua hasil penelitian ini yang di isi melalui angket atau quisioner. Para responden (mahasiswa) menjelaskan bahwa banyak sekali mahasiswa mahasiswa dari prodi jurnalistik ini menginginkan profesi jurnalistik lebih berkembang pesat di era digital ini, Dan hasil penelitian banyak mahasiswa yang sangat antusias untuk bagaimana profesi jurnalistik ini dapat membuka lapangan kerja pada mahasiswa mahasiwa yang nantinya akan lulus s1 dan mendapat kerja yang sesuai dengan prodi yang di jalankan dengan di permudah, Hasil penelitian ini juga menunjukan bahwa solusi untuk bertahan sebagai mahasiswa agar tidak tertinggalpada zaman di era digital ini ialah dengan terus mengikuti era atau zaman yang ada dengan cata mengembangkan dan meningkatkan krestifitas diri.